2015
DOI: 10.2169/internalmedicine.54.4891
|View full text |Cite
|
Sign up to set email alerts
|

False-positive Results Obtained for Immunoglobulin M Antibody Tests of Cerebrospinal Fluid for Herpes Simplex Virus in a Patient with Varicella Zoster Virus Encephalitis

Abstract: A 66-year-old man presented with a disturbed consciousness and seizure-like movements, followed by the initial symptoms of herpes zoster. Immunoglobulin (Ig) M antibodies to varicella zoster virus (VZV) as well as herpes simplex virus (HSV) were positive in the cerebrospinal fluid (CSF), whereas polymerase chain reaction of the CSF was positive for VZV-DNA but negative for HSV-DNA. The serum/CSF IgM ratio for VZV and HSV increased in association with a clinical improvement. This is a case report of a rare case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
(11 reference statements)
1
2
0
Order By: Relevance
“…It shall be noteworthy that previous clinical research studies have indicated a correlation between VZV infection and BBB disruption. In parallel, in the present study, the activated processes and pathways enriched in the PHN-CSF, such as coagulation, complement activation, infection and immune response, phagocytosis, and cholesterol metabolism, were similar to those in previous proteomic research investigating the plasma metabolism of the PHN patients . Besides, PLG and APOA1, the verified hub proteins, are reported to be mainly derived from the bloodstream rather than the CNS.…”
Section: Discussionsupporting
confidence: 85%
“…It shall be noteworthy that previous clinical research studies have indicated a correlation between VZV infection and BBB disruption. In parallel, in the present study, the activated processes and pathways enriched in the PHN-CSF, such as coagulation, complement activation, infection and immune response, phagocytosis, and cholesterol metabolism, were similar to those in previous proteomic research investigating the plasma metabolism of the PHN patients . Besides, PLG and APOA1, the verified hub proteins, are reported to be mainly derived from the bloodstream rather than the CNS.…”
Section: Discussionsupporting
confidence: 85%
“…The HSV-1 IgM test result was negative despite the presence of a life-threatening acute infection, whereas the HSV-2 IgM test result was positive. False-positive results have been reported for both HSV and VZV (28,29). Of note, IgM may not develop during active reactivation.…”
Section: Case Examplesmentioning
confidence: 99%
“…The results of subgroup analyses were consistent with this finding. In addition, no increased risk Many studies have explored the relationship between VZV infection and dementia because VZV can directly invade the brain and cause inflammation (Haanpää et al, 1998;Kinno et al, 2015). Previous studies reported viral replication in the cerebral arteries (Gilden et al, 2009;Stenmark et al, 2013).…”
Section: Discussionmentioning
confidence: 99%